Identification of a Major Locus, TNF1, That Controls BCG-Triggered Tumor Necrosis Factor Production by Leukocytes in an Area Hyperendemic for Tuberculosis - Cobat, Aurelie; Hoal, Eileen G.; Gallant, Caroline J.; Simkin, Leah; Black, Gillian F.; Stanley, Kim; Jaïs, Jean-Philippe; Yu, Ting-Heng; Boland-Auge, Anne; Grange, Ghislain; Delacourt, Christophe; van Helden, Paul; et al. (Clinical infectious diseases, 2013)
Background. Tumor necrosis factor (TNF) is a key immune regulator of tuberculosis resistance, as exemplified by the highly increased risk of tuberculosis disease among individuals receiving TNF-blocker therapy. Methods. We determined the extent of TNF production after stimulation with BCG or BCG plus interferon gamma (IFN-γ) using a whole blood assay in 392 children belonging to 135 nuclear families from an area hyperendemic for tuberculosis in South Africa. We conducted classical univariate and bivariate genome-wide linkage analysis of TNF production using the data from both stimulation protocols by means of an extension of the maximum-likelihood-binomial method for quantitative trait loci to multivariate analysis. Results. Stimulation of whole blood by either BCG or BCG plus IFN-γ resulted in a range of TNF release across subjects. Extent of TNF production following both stimulation protocols was highly correlated (r = 0.81). We failed to identify genetic linkage of TNF release when considering each stimulus separately. However, using a multivariate approach, we detected a major pleiotropic locus (P < 10 −5 ) on chromosome region 11p15, termed TNF locus 1 (TNF1), that controlled TNF production after stimulation by both BCG alone and BCG plus IFN-γ. Conclusions. The TNF1 locus was mapped in the vicinity of the TST1 locus, previously identified in the same family sample, that controls tuberculin skin test (TST) negativity per se, that is, T-cell—independent resistance to Mycobacterium tuberculosis infection. This suggested that there is a connection between TST negativity per se and TNF production.